KARAKTERISTIK IBU YANG MENGALAMI DEPRESI DALAM KEHAMILAN - Ratu Kusuma (Universitas Baiturrahim, 2019)
Depression in pregnancy is a mood disorder with symptoms of feeling sad, more sensitive so easily irritated even to crying, anxiety, lack of hope for the future, sleep disturbances in the form of nightmares or insomnia, decreased appetite, decreased libido, impaired social interaction, tired easily so that they experience interference in carrying out daily activities, impaired memory or difficulty concentrating, even some mothers experience hallucinations that risk the injury to themselves and others around them. Events in the world reached 23%, Asia 15-20%, Indonesia 25%, while in Riau Province around 20%. The purpose of this study is to identify the characteristics of mothers who experience depression during their pregnancy. It is a descriptive study, with consecutive sampling technique, conducted on 32 trimester II pregnant women (20-27 weeks) in Kecamatan Bangkinangand 22 pregnant women in Kecamatan Tapung I. The measurement of depression was done using Edinburgh postpartum depression scale (EPDS) which was declared valid and reliably used to measure depression in pregnancy. The results showed that the majority of pregnant women who experience depression are at the age of not at risk (20-35 years) as much as 60%, secondary education (80%), depression occurs in working mothers and not working each 50%, multigravida (70.00%), having 0-3 children, never experiencing abortion (90.00%), unwanted pregnancy (30.00%) and there are 10 (18.52%) trimester II pregnant women who experience depression during pregnancy. Depression experienced by pregnant women in Kecamatan Bangkinang and KecamatanTapung I is quite high, this is thought to be caused by maternal age, education, frequency of pregnancy, number of living children and unwanted pregnancy factors because some mothers do not want their pregnancy.